2015
DOI: 10.1007/s00439-015-1575-0
|View full text |Cite
|
Sign up to set email alerts
|

High diagnostic yield of clinical exome sequencing in Middle Eastern patients with Mendelian disorders

Abstract: Clinical exome sequencing (CES) has become an increasingly popular diagnostic tool in patients with heterogeneous genetic disorders, especially in those with neurocognitive phenotypes. Utility of CES in consanguineous populations has not yet been determined on a large scale. A clinical cohort of 149 probands from Qatar with suspected Mendelian, mainly neurocognitive phenotypes, underwent CES from July 2012 to June 2014. Intellectual disability and global developmental delay were the most common clinical presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
147
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 159 publications
(160 citation statements)
references
References 74 publications
(29 reference statements)
12
147
1
Order By: Relevance
“…21 However, we note here that we cannot exclude the possibility of dual diagnosis and the presence of more than one underlying causal mutation in consanguineous pedigrees as described recently. 22 Second, a distinct dysmorphology profile is present in each of the study families, and this will be much more likely to facilitate "matchmaking" as compared with some of the nonspecific phenotypes reported by Bloss et al (e.g., developmental delay and muscle atrophy).…”
Section: Discussionmentioning
confidence: 94%
“…21 However, we note here that we cannot exclude the possibility of dual diagnosis and the presence of more than one underlying causal mutation in consanguineous pedigrees as described recently. 22 Second, a distinct dysmorphology profile is present in each of the study families, and this will be much more likely to facilitate "matchmaking" as compared with some of the nonspecific phenotypes reported by Bloss et al (e.g., developmental delay and muscle atrophy).…”
Section: Discussionmentioning
confidence: 94%
“…A Clinical exome sequencing (CES) study in Middle Eastern patients with suspected Mendelian disorders showed that MANF was one of novel candidate disease genes [32]. MANF gene is mutated in intron regions in a 22-year-old woman presented with T2DM, obesity and other disease phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Its efficacy is especially augmented over gene-by-gene Sanger sequencing and the candidate gene approach7 in genetically heterogeneous diseases such as retinitis pigmentosa (RP) and congenital hearing loss. However, WES analysis fails to detect mutations in many families with hereditary diseases and an average detection rate of only 50–60% has been reported in various conditions 8. Moreover, WES analysis is not efficient for the identification of large deletions as a function of its design, mainly since the traditional WES analysis schemes are designed to identify single-nucleotide variations or those involving a few bases only.…”
Section: Introductionmentioning
confidence: 99%